Sewing friendship: Increasing inclusivity through creating shared social spaces for migrant and local populations in Durban - Tinashe Mutero, Innocent; Mchunu, Khaya Jean; Gunass Govender, Ivan (Critical Studies in Teaching and Learning, 2023)
Most women in South Africa are heavily burdened by unemployment, poverty, and inequality. However, African immigrant women in South Africa are faced with additional challenges such as xenophobic discrimination, economic and social exclusion ,and poor integration of migrants in workspaces occupied by locals. This study took advantage of the growing demand for higher education to embrace engaged scholarship to embark on an engagement process that facilitated transformational learning by enabling experience sharing among a diverse group of local and foreign women from Thusa Batho Sewing for Africa, a community sewing project located in Durban. Results for this study, which was designed as a participatory action research, reveal the university’s agency in nurturing associational enterprises that facilitate social change. Further, results show that inclusive shared social spaces can be used as resources to facilitate both individual and group change through initiating shared problem identification and solving processes that can have a long-term impact on the community.